Nucleação e crescimento de nanohíbridos núcleo/casca Au@ZnS por rota coloidal aquosa mediada por carboximetilcelulose e estudo de propriedades nanofotônicas - Anderson Caires de Jesus (2020)
Nowadays, the development of new nanostructured materials is vital for nanotechnology applications. In this sense, colloidal dispersions of ZnS quantum dots (QDts) and gold nanoparticles (AuNPs), have been extensively studied due to their optical properties and biofunctionalization capacity. In this work, the synthesis of aqueous colloidal dispersions of AuNPs, ZnS QDts and nanoheterojunctions (Au@ZnSCMC) were carried out by aqueous colloidal route mediated by carboxymethylcellulose (CMC) biopolymer. The nanostructured materials were characterized by morphological, spectroscopic, and chemical techniques. The results demonstrate 20 nm diameter crystalline metallic nanostructures, stable and with physicochemical, colloidal and optical properties dependent on the pH and the degree of substitution of the CMC polymer chains associated with the protonation/deprotonation effect of the carboxylate groups (COO- /COOH), in the nucleation and colloidal growth mechanism. AuNPs@CMC nanoconjugates with the glycoprotein gp41 and anti-HIV1 antibodies, were applied as a biosensor for HIV detection, with sensitivity in the order of pM, through light scattering in colloidal dispersion. The synthesis of ZnS QDts, presented nanocrystals with a diameter around 3 nm and optical properties dependent on the synthesis conditions, with significant light emission (~ 430 nm) and quantum yield (QY) of 0.3%, being applied to bioimaging of glioma cancer cells. The chemical conditions of the polymeric chain (RCOO- → COOH), combined with the reaction stoichiometry (Zn:S), had a fundamental effect on the nucleation and growth of ZnS@CMC QDts, influencing the optical properties. The 2.5 nm thick nanocrystalline ZnS shell ensured quantum confinement in the Au@ZnS-CMC nanoheterojunction, resulting in light emission (~ 430 nm), with plasmon/exciton coupling and charge/energy transfer mechanisms in the interface influencing plasmon resonance and photoluminescent emission. The inclusion of trivalent ions (In3+) in the crystalline structure of the shell resulted in the adjustment of the band gap and in the suppression of light emission (quenching), due to the complex structure of defects.